2022
DOI: 10.3390/su142215038
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality and Environmental Effects Due to COVID-19 in Tehran, Iran: Lessons for Sustainability

Abstract: The 2019 coronavirus disease (COVID-19) global pandemic spread can be considered a disastrous crisis that, in a given geographical area, significantly affects the increase in mortality rate with direct and indirect impacts on different scales and social, economic, political, and ecological factors. The effects of this crisis can be more intense in urban areas with high population density. Due to the more significant presence of vulnerable groups, the risk of death increases significantly. This research describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…COVID-19 could have some positive environmental impacts due to its reduced energy consumption, according to initial reports. It has been observed that the CO 2 , NO 2 , and PM2.5 emissions in China have been drastically reduced as a result of the halting of the power plant and industrial activities also decreased utilization of vehicles, although such a short-term decline in emissions would not be a sustainable way for the protection of the environment since the outbreak of COVID-19 has occurred [71]. COVID-19 also improved Tehran's air quality indicators.…”
Section: Recent Developments In Environmental Issues Relating To Covi...mentioning
confidence: 99%
“…COVID-19 could have some positive environmental impacts due to its reduced energy consumption, according to initial reports. It has been observed that the CO 2 , NO 2 , and PM2.5 emissions in China have been drastically reduced as a result of the halting of the power plant and industrial activities also decreased utilization of vehicles, although such a short-term decline in emissions would not be a sustainable way for the protection of the environment since the outbreak of COVID-19 has occurred [71]. COVID-19 also improved Tehran's air quality indicators.…”
Section: Recent Developments In Environmental Issues Relating To Covi...mentioning
confidence: 99%